THE EVALUATION OF THE TO DEVELOP MORALITY TO LEAD GOOD CHILDREN SRI RAJAPRAJA PROJECT IN RAJAPRAJANUGROH SCHOOL 35 - Ramtad, Churiphon; Navakitpaiboon , Nilrat; Chairueang, Nopparat (Journal of Educational Review Faculty of Education in MCU, 2026)
This research aims to evaluate participants in the Moral Development Project for Good Children at Rajaprajanugroh 35 School across four aspects: 1) evaluation during project implementation, 2) overall evaluation, 3) internal criteria evaluation, and 4) cost-effectiveness evaluation of the project regarding the development of morality and ethics among students at Rajaprajanugroh 35 School. This study employs a developmental research design, consisting of: 1) a quantitative approach using questionnaires, and 2) a qualitative approach using interviews. The research sample consisted of 16 teachers and 70 students, totaling 86 participants. The research instruments included questionnaires and interviews. Data analysis employed the mean, standard deviation, and content analysis. The research findings revealed that: 1) The evaluation results during project implementation were overall at a high level. Considering individual aspects, the highest average score was for community feedback, followed by the monitoring, evaluation, and follow-up of activities organized in collaboration with the community. The aspect with the lowest average score was the appropriateness of the timeframe. 2) The overall evaluation of the project indicated a high level. Considering individual aspects, the highest average scores were for students’ polite, kind, and respectful behavior towards others, followed by their kindness and respect for others’ opinions, and their willingness to follow rules and contribute to a positive classroom atmosphere. Students were able to apply moral and ethical principles in daily life, uphold honesty, and serve as good role models. The aspect with the lowest average score was students’ valuation of honesty and responsibility. 3) The internal criteria evaluation of the project showed an overall high level. Considering individual aspects, the highest average scores were for students’ appropriate behavior in the classroom and during group activities, as well as their satisfaction and happiness derived from moral and ethical principles. This was followed by students being kind, helpful, and positive inspirations to their classmates. The aspect with the lowest average score was students’ appreciation and acceptance of personal moral behaviors. 4) The cost-effectiveness evaluation of the project revealed an overall high level. Considering individual aspects, the highest average score was for students’ creativity, followed by their morality and ethics, their ability to thoughtfully apply acquired knowledge to solve problems, and their learning and self-development. The aspect with the lowest average score was students’ teamwork ability.